Human hepatocyte assessment of imatinib drug–drug interactions – complexities in clinical translation. (19th September 2015) - Beumer, Jan H.; Pillai, Venkateswaran C.; Parise, Robert A.; Christner, Susan M.; Kiesel, Brian F.; Rudek, Michelle A.; Venkataramanan, Raman
Abstract : Aim: Inducers and inhibitors of CYP3A, such as ritonavir and efavirenz, may be used as part of the highly active antiretroviral therapy (HAART) to treat HIV patients. HIV patients with chronic myeloid leukemia or gastrointestinal stromal tumour may need imatinib, a CYP3A4 substrate with known exposure response–relationships. Administration of imatinib to patients on ritonavir or efavirenz may result in altered imatinib exposure leading to increased toxicity or failure of therapy, respectively. We used primary human hepatocyte cultures to evaluate the magnitude of interaction between imatinib and ritonavir/efavirenz. Methods: Hepatocytes were pre‐treated with vehicle, ritonavir, ketoconazole, efavirenz or rifampicin, and the metabolism of imatinib was characterized over time. Concentrations of imatinib and metabolite were quantitated in combined lysate and medium, using LC‐MS. Results: The predicted changes in imatinib CLoral (95% CI) with ketoconazole, ritonavir, rifampicin and efavirenz were 4.0‐fold (0, 9.2) lower, 2.8‐fold (0.04, 5.5) lower, 2.9‐fold (2.2, 3.5) higher and 2.0‐fold (0.42, 3.5) higher, respectively. These predictions were in good agreement with clinical single dose drug–drug interaction studies, but not with reports of imatinib interactions at steady‐state. Alterations in metabolism were similar after acute or chronic imatinib exposure. Conclusions: In vitro human hepatocytes predicted increased clearance of imatinib with inducers and decreased clearance with inhibitors of CYP enzymes. The impact of HAART on imatinib may depend on whether it is being initiated or has already been dosed chronically in patients. Therapeutic drug monitoring may have a role in optimizing imatinib therapy in this patient population.